2020
DOI: 10.1080/00268976.2020.1825850
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state dynamics of isolated and (micro)solvated methyl sinapate: the bright and shady sides of a natural sunscreen

Abstract: The increasing awareness of the adverse effects of exposure to UV radiation in combination with the conclusion that presently employed sunscreen agents are far from optimal has led to the need to develop novel UV filters with improved absorption and stability characteristics. Studies of natural sunscreens can provide fundamental insight into strategies to come to a rational design of such filters. Here, we use high-resolution laser spectroscopic methods to study the spectroscopy and excited-state dynamics of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…Fig. 1 displays to this purpose the R2PI spectrum of MS as reported previously 37,57 together with UV-D spectra of the syn/cis, anti/cis and anti/trans conformations, the cis conformations being dominantly present while the trans conformation is only present in minor amounts.…”
Section: A Zeke View On the Spectroscopic Properties Of The S 1 And D 0 States Of Ms Conformersmentioning
confidence: 82%
See 2 more Smart Citations
“…Fig. 1 displays to this purpose the R2PI spectrum of MS as reported previously 37,57 together with UV-D spectra of the syn/cis, anti/cis and anti/trans conformations, the cis conformations being dominantly present while the trans conformation is only present in minor amounts.…”
Section: A Zeke View On the Spectroscopic Properties Of The S 1 And D 0 States Of Ms Conformersmentioning
confidence: 82%
“…Methyl sinapate was synthesized according to previously reported procedures. 57,65 R2PI, UV-depletion (UV-D), and ZEKE-PFI spectroscopy has been performed using a molecular beam setup described in detail before, 34,66 and therefore only details pertaining to the present experiments will be provided. Briefly, in the current study the sample was heated in a glass container to a temperature of 140 1C and seeded into a supersonic expansion of 1.5 bar neon using a General Valve pulsed nozzle with an orifice diameter of 0.5 mm that was kept 5 1C higher in temperature to avoid clogging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,31 In this context, a number of theoretical studies have investigated with a variety of techniques, including high-level quantum chemical approaches (complete active space selfconsistent field (CASSCF) and multi-state complete active space 2nd-order perturbation (MS-CASPT2)), the photophysical and photochemical properties of several cinnamate derivatives and/or reduced models of OMC -namely molecular structures including only the cinnamate chromophore nucleus but not the long aliphatic chain. [32][33][34][35][36][37][38][39][40][41][42][43] For example, the trans-cis photoisomerization route of substituted methylcinnamates was recently explored via single-component artificial force-induced reaction (SC-AFIR) combined with timedependent density functional theory (TD-DFT), highlighting a marked influence of the phenyl substituents on the decay mechanism. 42 Other studies at the TD-DFT/CIS level suggested appreciable solvent and hydrogen-bond effects on the photoisomerization mechanisms, 28,29 which were then corroborated by CASSCF and MS-CASPT2 calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the conclusion that the microenvironment was intrinsically promoting efficient ultrafast decay for this sunscreen. More recently, Buma and co-workers have used resonance enhanced multiphoton ionization to investigate an isolated complex of the UV filter methyl sinapate with a single water molecule (Fan et al, 2021), again observing how solvent complexation perturbs the electronic properties. One of the considerable advantages of such gas-phase studies is that they allow direct comparison with high-level computational chemistry calculations.…”
Section: How Does Changing the Solvent Affect Sunscreen Performance?mentioning
confidence: 99%